Broadband Passive Photonic Diodes With the Saturable Absorption in Antimony Thin Film - Jinrui Zhang; Jie Li; Lili Miao; Chujun Zhao (IEEE Photonics Journal)
The low-dimensional nonlinear optical materials can provide a cost-effective and feasible way to realize the broadband optoelectronic devices. Here, we investigated the broadband nonlinear optical absorption of antimony thin film, and fabricated a broadband passive photonic diode with antimony thin film to achieve the all-optical nonreciprocal function with optical nonreciprocity factor about 5 dB at 780 nm and 2 dB at 1560 nm, respectively. The experimental results show the potential applications of antimony-based materials in broadband passive photonic diodes, and may make inroads for the cost-effective and reliable broadband optoelectronic devices.